2018
DOI: 10.1111/1440-1681.12911
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricaemia and development of type 2 diabetes mellitus in Asian population

Abstract: Recently, meta-analysis studies reported that hyperuricaemia is associated with higher incidence of type 2 diabetes mellitus (T2DM), however, there are limited data on the Asian population. The aim of this observational study is to estimate the long-term impact of hyperuricaemia on the new-onset T2DM and cardiovascular events. This study is based on a single-centre, all-comers, and large retrospective cohort. Subjects that visited from January 2004 to February 2014 were enrolled using the electronic database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 31 publications
5
26
1
3
Order By: Relevance
“…16 A retrospective study consisting of 10,505 participants enrolled at a cardiovascular center without history of diabetes at baseline also found that the risk of diabetes increased when UA increased only in the female subgroup. 17 Although the present study did not find a significant interaction between sex and UA on diabetes incidence, stratified analyses across sex showed that higher circulating UA levels were independently associated with increased risks of diabetes incidence in men but not in women, which were controversial with the previous two reports above. The possible reasons for the conflicting findings between ours and others may be due to: the diabetes incidence rate in men in the present study was relatively higher than that in women as shown in Table 2.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…16 A retrospective study consisting of 10,505 participants enrolled at a cardiovascular center without history of diabetes at baseline also found that the risk of diabetes increased when UA increased only in the female subgroup. 17 Although the present study did not find a significant interaction between sex and UA on diabetes incidence, stratified analyses across sex showed that higher circulating UA levels were independently associated with increased risks of diabetes incidence in men but not in women, which were controversial with the previous two reports above. The possible reasons for the conflicting findings between ours and others may be due to: the diabetes incidence rate in men in the present study was relatively higher than that in women as shown in Table 2.…”
Section: Discussioncontrasting
confidence: 99%
“…16 Choi et al also found that hyperuricemia was a significantly independent predictor of diabetes only in the female subgroup. 17 Therefore, there is genuine need to clarify the sex specific associations of circulating UA with diabetes, especially from prospective cohort studies on different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid (SUA), an end product of the metabolism of purine nucleotides, has been suggested as a risk factor for T2DM in an increasing number of epidemiological studies [ 2 6 ]. To our knowledge, some cohort studies have investigated the association but with relatively small sample sizes ranging from 711 to 12,643 and inconsistent findings reported [ 2 5 , 7 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, some cohort studies have investigated the association but with relatively small sample sizes ranging from 711 to 12,643 and inconsistent findings reported [ 2 5 , 7 14 ]. Evidence on the sex-specific differences in the SUA level-T2DM risk association is limited and has resulted in conflicting findings [ 2 , 5 , 6 , 12 , 15 , 16 ], with studies showing a significant association in both sexes [ 12 ], only women [ 2 ], or only men [ 4 , 5 , 15 ]. Therefore, more studies are warranted to clarify the sex-specific association between SUA level and T2DM risk.…”
Section: Introductionmentioning
confidence: 99%
“…SUA level was recorded in mg/dl and can be converted to µmol/L by multiplying with 59.485. Although consensus on the definition of hyperuricemia is scarce [18], serum uric acid levels � 7 mg/dl in men and SUA � 6.5 mg/dl in women was considered as hyperuricemia [19].…”
Section: Data Collection and Variables Analyzedmentioning
confidence: 99%